Sex and bacterial infectious diseases - Mege, J.-L. (New Microbes New Infect, 2018)
Most infectious diseases are unequally distributed between male and female subjects. This sex dimorphism is confirmed by epidemiologic studies which suggest an increased number of male septic patients, while, due to the class age of septic patients, an overrepresentation of female patients would be expected. Lifestyle, recreational activities, professional exposition and access to care are plausible reasons for this dimorphism. However, biological differences should be carefully considered, particularly the weight of X-linked variability and the role of sex hormones. Animal models clearly show that clinical response to infection is more exuberant in males than in females. This is partly explained by an attenuation of the inflammatory response by female sex hormones. However, the translation from experimental studies to the bedside remains challenging as a result of confounding factors like age, hormone changes and response to treatment.